Sometimes you may be given one endpoint and the midpoint, and have to work out the other endpoint. To get from the first endpoint (1,3) to the midpoint (3,7), we move 2 in the x

Assuming you have an endpoint A = (x₁, y₁) and midpoint M = (x, y): Double midpoints' coordinates: 2x, 2y. Subtract the x-coordinate of the known endpoint from the first

If you know one endpoint (x1,y1) and the midpoint (a,b), but you do not know the other endpoint (x2,y2), then by rewriting the midpoint formula: {a = x1+x2 2 ⇒ 2a = x1 + x2 ⇒